Chemical Systems and Related Techniques for Assisting Simple Visual Detection of Trace Metal Ions - MIZUGUCHI, Hitoshi (BUNSEKI KAGAKU, 2024)
This article reviews analytical methods developed to measure trace metal ions quickly by simple operations. To ensure sensitivity and selectivity towards the target metal ions, the techniques utilize the kinetic difference of the dissociation reaction of metal complexes, the interaction between the solid surface and the metal complexes, and the synergistic effect of spectral characteristics with complex formation equilibrium. Examples include quantitative analysis using thin-layer chromatography and enrichment on membrane filters and a visual threshold detection method for trace metal ions using homo-binuclear complex formation systems.